After South China Sea Ruling – Good Fences or Good Neighbours: Implications for Maritime Boundaries - Bateman, Sam (2016)
The 12 July 2016 arbitral tribunal ruling in The Hague has specified that there are no islands in the Spratly group capable of generating a full set of maritime zones. This has theoretically helped agreement on maritime boundaries in the South China Sea but many problems still remain.